2016
DOI: 10.1103/physreva.93.023812
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast saturation of electronic-resonance-enhanced coherent anti-Stokes Raman scattering and comparison for pulse durations in the nanosecond to femtosecond regime

Abstract: The saturation threshold of a probe pulse in an ultrafast electronic-resonance-enhanced (ERE) coherent antiStokes Raman spectroscopy (CARS) configuration is calculated. We demonstrate that while the underdamping condition is a sufficient condition for saturation of ERE-CARS with the long-pulse excitations, a transient gain must be achieved to saturate the ERE-CARS signal for the ultrafast probe regime. We identify that the area under the probe pulse can be used as a definitive parameter to determine the criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Also, it has been shown that in an electronic-resonanceenhanced CARS (ERE-CARS) configuration, where the probe pulse resonantly couples the ground and electronically excited electronic states of the molecule, a strong ns-duration probe can saturate the signal [163]. However, in a detailed theoretical study of ERE-CARS for different pulse regimes with durations ranging from 10 ns-10 fs, it was shown that the signal saturation threshold associated with probe pulse begins to increase for pulse durations shorter than the molecular decay and dephasing times; the threshold intensity was shown to increase quadratically with the inverse of the pulse duration [164]. It has also been shown that the saturation threshold of the pump and Stokes intensities for Raman coherence using ultrafast pulses has a similar dependence [106].…”
Section: Saturation-free Fs-cars Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it has been shown that in an electronic-resonanceenhanced CARS (ERE-CARS) configuration, where the probe pulse resonantly couples the ground and electronically excited electronic states of the molecule, a strong ns-duration probe can saturate the signal [163]. However, in a detailed theoretical study of ERE-CARS for different pulse regimes with durations ranging from 10 ns-10 fs, it was shown that the signal saturation threshold associated with probe pulse begins to increase for pulse durations shorter than the molecular decay and dephasing times; the threshold intensity was shown to increase quadratically with the inverse of the pulse duration [164]. It has also been shown that the saturation threshold of the pump and Stokes intensities for Raman coherence using ultrafast pulses has a similar dependence [106].…”
Section: Saturation-free Fs-cars Spectroscopymentioning
confidence: 99%
“…From careful theoretical analysis it was demonstrated that ERE-CARS is dependent on the coherencedephasing rate but independent of the electronic quenching rate, and such dephasing dependence can be overcome by operating near the saturation condition for probe coupling [163,253]. The saturation conditions for the probe pulse in ERE-CARS have been analyzed theoretically for pulse durations ranging from ns to fs [164]. It is observed that for pulse durations longer that collisional timescales, the threshold intensity for saturation is independent of the duration of the pulse; however, for pulse durations shorter than collisional timescales, the threshold intensity of saturation is inversely proportional to the square of the pulse duration.…”
Section: Prospects For Collision-free Measurements Of Other Chemical mentioning
confidence: 99%
“…A generalized formulation is developed for determining the saturation thresholds for optical processes excited by ultrafast pulses based on the pulse area of the excitation pulse [30] and for different pulse shapes [31]. The condition was derived for the saturation threshold of a probe pulse in an ultrafast electronic-resonance-enhanced (ERE) coherent anti-Stokes Raman spectroscopy (CARS) configuration [32]. Further, femtosecond fully resonant electronically enhanced CARS (FREE-CARS) has been demonstrated with orders of magnitude enhancement of the CARS signal, where all three input pump, Stokes, and probe pulses are resonant to electronic states of the molecules [33,34].…”
Section: Introductionmentioning
confidence: 99%